Prediction of the occurrence of calcium oxalate kidney stones based on clinical and gut microbiota characteristics - Xiang, Liyuan; Jin, Xi; Liu, Yu; Ma, Yucheng; Jian, Zhongyu; Wei, Zhitao; Li, Hong; Li, Yi; Wang, Kunjie (World journal of urology, 2022)
Purpose To predict the occurrence of calcium oxalate kidney stones based on clinical and gut microbiota characteristics. Methods Gut microbiota and clinical data from 180 subjects (120 for training set and 60 for validation) attending the West China Hospital (WCH) were collected between June 2018 and January 2021. Based on the gut microbiota and clinical data from 120 subjects (66 non-kidney stone individuals and 54 kidney stone patients), we evaluated eight machine learning methods to predict the occurrence of calcium oxalate kidney stones. Results With fivefold cross-validation, the random forest method produced the best area under the curve (AUC) of 0.94. We further applied random forest to an independent validation dataset with 60 samples (34 non-kidney stone individuals and 26 kidney stone patients), which yielded an AUC of 0.88. Conclusion Our results demonstrated that clinical data combined with gut microbiota characteristics may help predict the occurrence of kidney stones.